PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ACCELERATED TEACHING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS VII-D SMP NEGERI 3 SITUBONDO SEMESTER GANJIL PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL (IPS EKONOMI) - sahwari sahwari (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2015)
Learning Social Sciences can guide students to have critical thinking skills. Think critically in response to problems and apply in the community as a form of application. Unfortunately, this dream was not realized. This is because teachers have difficulty in choosing a learning model and only use one learning model in teaching. This research design is a descriptive model. This research was conducted at SMP Negeri 3 Situbondo with the object of research being class VII-D students. Data collection using tests, observation, interviews, and documentation. This research data analysis using qualitative descriptive analysis. The results showed that student learning outcomes had met the standard of success, namely> 75% classical completeness. Increased learning activities can be seen from the development before action and after action. Before the action of student learning activities, both individually and classically, they were still below the completeness standard of 75%. In cycle 1, out of 30 students, there were 16 students who completed their studies or 53% who obtained a value> 75, while 13% or as many as 4 students did not. Student learning activities in cycle 1 are still classified as very low, this is indicated by active participation and learning skills of 53% and 48%. The low level of student learning activities is due to the fact that students are still adjusting themselves to the group so that there is a need for an increase in learning activities by means of the teacher being a facilitator and giving students the opportunity to choose a leader in their own group. Increased social interaction and exchanging of ideas in answering questions with peers, learning skills shown in making their own questions, understanding questions, neatness and systematic writing of answers and the ability to think creatively in both doing practice questions and tests showed an increase of 62%. Based on the results of the research and discussion, it can be concluded that the application of the Accelerated Teaching learning model can improve learning activities and student learning outcomes in Economics class VII-D at SMP Negeri 3 Situbondo odd semester.